Implementation of Industrial Hygiene on Construction Sites - Sahrom, Mat Idris; Rozlin Zainal,; Kasim, Narimah; Abdul Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2022)
Industrial hygiene is one of the important parts of construction sites as it be able to keep the sites healthy and safe. Nowadays, industrial hygiene is difficult to properly implement on construction sites because of the lack of awareness by employers and employees of keeping the sites healthy. As a result, this study aims to identify the problems associated with industrial hygiene on construction sites, identify solutions for the construction sites. The data for this study was gathered solely through a questionnaire. The respondents to this study are focused on 291 contractors G5 that was actively registered under CIDB in the Federal Territory of Kuala Lumpur. The questionnaire successfully collected only 152 respondents. Therefore, the response rate for this study is 66%. Descriptive statistic and crosstabs by SPSS software was used to analyse the data for all objectives. This research finds that the main problems of implementation that occur for industrial hygiene on the construction site for the workers is deplorable in living conditions and main strategies is improve workers’ performance. The relationship proved that three main problems are deplorable in living conditions, inadequate storage system and lack of organisation cleanliness encouragement are related with the main strategies. The findings of this study will raise awareness among construction site employers and the government, contractors, and workers about the importance of maintaining healthy hygiene on the job site. Hopefully, the strategies for industrial hygiene problems on the construction sites could be taken instantly.